Recent advances in biochar application for water and wastewater treatment: a review - Wang, Xiaoqing; Guo, Zizhang; Hu, Zhen; Zhang, Jian (PeerJ (San Francisco, CA), 2020)
In the past decade, researchers have carried out a massive amount of research on the application of biochar for contaminants removal from aqueous solutions. As an emerging sorbent with great potential, biochar has shown significant advantages such as the broad sources of feedstocks, easy preparation process, and favorable surface and structural properties. This review provides an overview of recent advances in biochar application in water and wastewater treatment, including a brief discussion of the involved sorption mechanisms of contaminants removal, as well as the biochar modification methods. Furthermore, environmental concerns of biochar that need to be paid attention to and future research directions are put forward to promote the further application of biochar in practical water and wastewater treatment.